Developing Social Solidarity through Digital Media - Eni Maryani (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2018)
This research raises the issue on digital media by activists in an effort to gain wider public involvement towards the social transformation process based on social solidarity. The development of digital media broadens the space to raise a range of marginal issues in public spaces controlled by predominant social groups. Digital media provides elite and mainstream media an opportunity for counter public spheres to dominate issues. Data collection is conducted through interviews and observation. There are both opportunities and challenges in utilizing digital media in building social solidarity. Characteristics of digital media allows a faster reach of a wider and diverse audience as well as generate an increasingly fierce global competition. Technologically, digital media only gives a very short opportunity to hold the audience’ attention. Therefore, communication between humans is still needed to strengthen and build public trust. The occurrence of a communication has significant effect when online media that are parallel with activities and issues that are offline, demands both forms of communication to be used simultaneously.